Effect of uv aging on the physical properties of polypropylene/zinc borate polymer composites - ULUTAŞ, ELİF; TAŞDEMİR, MÜNİR (My University, 2023)
Plastics, which have a wide range in terms of production methods, have replaced traditional materials because their chemical and physical properties can be changed in the desired direction. The structural changes that occur when functional filler additives are used during production cause improvements in many physical properties of the new plastic. Using boron and boron compounds as additives positively affects the mechanical, thermal, electrical, optical, and physical properties of polymer composites. As it is known, plastics, which are flammable by nature, have a low oxygen index and therefore pose a danger to human life and the environment due to the threat of fire. In this study, the effects of zinc borate, which has flameretardant properties, on the physical and morphological properties of polypropylene were investigated. In addition, the effects of aging were investigated by UV aging at 70°C for 15 and 30 days on the polymer composites produced in the study. PP/ZnB polymer composites with different concentrations (5, 10, 15, and 20%) were produced in a twin screw extruder to provide a more homogeneous mixture. Test samples of polymer composites, which were granulated with the help of a grinder, were successfully molded in the injection machine. Limit oxygen index (LOI) to examine the flaming behavior of the samples, heat deflection temperature (HDT), Vicat softening point, melt flow index (MFI) test to examine the thermal behavior, moisture content, and density test to examine the physical properties of the samples were performed. The microstructure examination of polymer composites was made with a scanning electron microscope (SEM).
Keywords: Polypropylene; polymer composites; zinc borate; physical properties; UV aging